FUNGSI MAKNA DAN SIMBOL PADA KARWAR (Function and Meaning of Karwar Symbol) - Rini Maryone (BALAI ARKEOLOGI PAPUA, 2014)
The existence of natural caves and niches wild in Biak and interesting enough, one of which is on the site Cave Yenukem, Makmakerbo village. On the site is found in the form of rock art paintings karwar on boulders. Karwar rock art painting is a relic of prehistoric ancestors, who came from the monumental character of the neolithic culture. Regarding the remains of rock art paintings karwar mystery writer tries to analyze the function, and symbols that can be known and studied by the younger generation, which contained educative function containing moral education for human life. The method of data collection is done with literature, field surveys, and analysis using Ethnoarchaeology approach. Painting sculpture karwar a relic of prehistoric ancestors. Karwar so basic concepts of trust in the Biak past so they created a form of sculpture called amflanir / karwar to commemorate those who died.ABSTRAKKeberadaan gua-gua alam maupun ceruk-ceruk alam di wilayah Biak cukup banyak dan menarik, salah satunya adalah di situs Gua Yenukem Desa Makmakerbo. Di situs tersebut ditemukan berupa lukisan seni cadas karwar pada bongkahan batu. Lukisan seni cadas karwar merupakan peninggalan dari nenek moyang dari jaman prasejarah, yang bercorak monumental berasal dari kebudayaan neolitik. Mengenai tinggalan seni cadas lukisan karwar penulis mencoba mengupas misteri akan fungsi, dan simbol sehingga dapat di ketahui dan dipelajari oleh generasi muda, yang termuat fungsi edukatif yang berisikan pendidikan moral bagi kehidupan manusia. Metode pengumpulan data dilakukan dengan studi pustaka, survei lapangan, dan analisis menggunakan pendekatan etnoarkeologi. Lukisan patung karwar merupakan peninggalan dari nenek moyang dari jaman prasejarah. Konsep kepercayaan karwar begitu mendasar pada orang Biak masa lampau sehingga mereka menciptakan suatu bentuk patung yang di sebut amflanir/ karwar untuk memperingati orang yang meninggal.